Altered Expression of Specific MicroRNAs in Plasma of Aneurysmal Subarachnoid Hemorrhage Patients - Zheng, Lina; Zhang, Xin; Liu, Liping; Pu, Yuehua (Frontiers in Neurology, 2022)
Background Aneurysmal subarachnoid hemorrhage (aSAH) is a life-threatening condition with high disability and mortality. MicroRNAs (miRNAs) are reported to play a modulating role in aSAH. We investigated specific plasma microRNAs (miRNAs) associated with aSAH and gained comprehensive insight into its pathological mechanisms. Methods This is a prospective case–control study. We used a two-stage approach, with primary screening and ensuing two-step validation stages. Significantly differentially expressed plasma miRNAs between aSAH patients and neurologically healthy controls were initially screened by microarray analysis. These miRNAs were then validated in two groups of independent cohorts using reverse transcription quantitative real-time polymerase chain reaction assays. Functional annotation of these miRNA targets was performed by Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment analyses. Results In the primary screening stage, 14 miRNAs were identified as differentially expressed at a significance level of P < 0.05 and fold change >2 between 5 aSAH patients and 5 neurologically healthy controls. In the two validation steps (20 patients vs. 20 control; 40 patients vs. 30 controls), miR-23b-3p, miR-590-5p, miR-20b-5p, miR-142-3p, and miR-29b-3p were found to be significantly down-regulated in patients with aSAH compared with controls. Through these 5 miRNAs, we obtained 32 overlapping target genes, including TGM2, EREG, EDN1, and COL4A1, in three databases that may affect the progression of aSAH. The results of functional annotation revealed mechanisms mainly related to inflammation, smooth muscle cell proliferation and cell adhesion, potentially contributing to the occurrence of aSAH. Conclusion We demonstrate that specific miRNAs in plasma, including miR-23b-3p, miR-590-5p, miR-20b-5p, miR-142-3p, and miR-29b-3p, are significantly down-regulated in aSAH patients and may play a modulating role in its progression.